PENGARUH INFORMATION, MEDIA, DAN TECHNOLOGY LITERACY TERHADAP KOMPETENSI PEDAGOGIK GURU - Dewi Sulistiyarini; Febrianto Sabirin (Jurnal Teknologi Informasi dan Pendidikan, 2018)
This study aims to find out effect of information on literacy, technology literacy, and media literacy together on the pedagogic competence of junior high school teachers in Kubu Raya District. Research will be conducted on junior high school teachers in Kubu Raya District. The research method used is the ex-postfacto method with comparative comparational research forms. The total population of the study was 1041 people in 5 sub-districts. The sample used is 290 people and selected using simple random sampling technique. The results showed that there was a significant effect between information literacy, technology literacy, and media literacy on the pedagogic competence of junior high school teachers in Kubu Raya District. The amount of effect is 52.3% with a regression model that is Y = 2.114 + 0.816X1 + 0.186X2 + 0.183X3 which can be generalized to the study population.